Wall teichoic acids govern cationic gold nanoparticle interaction with Gram-positive bacterial cell walls. Issue 16 (3rd April 2020) - Caudill, Emily R.; Hernandez, Rodrigo Tapia; Johnson, Kyle P.; O'Rourke, James T.; Zhu, Lingchao; Haynes, Christy L.; Feng, Z. Vivian; Pedersen, Joel A.
Abstract : Cationic gold nanoparticle interaction with strains of Bacillus subtilis is dictated by wall teichoic acid structure and composition. Abstract : Molecular-level understanding of nanomaterial interactions with bacterial cell surfaces can facilitate design of antimicrobial and antifouling surfaces and inform assessment of potential consequences of nanomaterial release into the environment. Here, we investigate the interaction of cationic nanoparticles with the main surface components of Gram-positive bacteria: peptidoglycan and teichoic acids. We employed intact cells and isolated cell walls from wild type Bacillus subtilis and two mutant strains differing in wall teichoic acid composition to investigate interaction with gold nanoparticles functionalized with cationic, branched polyethylenimine. We quantified nanoparticle association with intact cells by flow cytometry and determined sites of interaction by solid-state 31 P- and 13 C-NMR spectroscopy. We find that wall teichoic acid structure and composition were important determinants for the extent of interaction with cationic gold nanoparticles. The nanoparticles interacted more with wall teichoic acids from the wild type and mutant lacking glucose in its wall teichoic acids than those from the mutant having wall teichoic acids lacking alanine and exhibiting more restricted molecular motion. Our experimental evidence supports the interpretation that electrostatic forces contributed to nanoparticle–cell interactions and that the accessibility of negatively charged moieties in teichoic acid chains influences the degree of interaction. The approaches employed in this study can be applied to engineered nanomaterials differing in core composition, shape, or surface functional groups as well as to other types of bacteria to elucidate the influence of nanoparticle and cell surface properties on interactions with Gram-positive bacteria.